2019
DOI: 10.1016/j.jesp.2019.103880
|View full text |Cite
|
Sign up to set email alerts
|

Loss framing increases self-serving mistakes (but does not alter attention)

Abstract: In ambiguous settings, people are tempted to make self-serving mistakes. Here, we assess whether people make more self-serving mistakes to minimize losses compared with maximize gains. Results reveal that participants are twice as likely to make self-serving mistakes to reduce losses compared to increase gains. We further trace participants' eye movements to gain insight into the process underlying self-serving mistakes in losses and gains. We find that tempting, self-serving information does not capture more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 58 publications
5
14
1
Order By: Relevance
“…To test this hypothesis, we estimated the ratio of self‐serving (i.e., asking for extra points in easy rounds) to self‐hurting (i.e., not asking for extra points in difficult rounds) errors. Similar to a previous study (Hochman et al, 2016; Leib et al, 2019), we observed that in both experiments, self‐serving errors were committed approximately twice as frequently as self‐hurting errors. This finding indicates that at least a portion of the rule violations reflects either conscious or unconscious self‐serving biases.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…To test this hypothesis, we estimated the ratio of self‐serving (i.e., asking for extra points in easy rounds) to self‐hurting (i.e., not asking for extra points in difficult rounds) errors. Similar to a previous study (Hochman et al, 2016; Leib et al, 2019), we observed that in both experiments, self‐serving errors were committed approximately twice as frequently as self‐hurting errors. This finding indicates that at least a portion of the rule violations reflects either conscious or unconscious self‐serving biases.…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies have shown that people make more self‐serving than self‐hurting errors (Hochman, Glockner, Fiedler, & Ayal, 2016; Leib, Pittarello, Gordon‐Hecker, Shalvi, & Roskes, 2019). This increased frequency of self‐serving errors has been explained as dishonest behavior aiming at maximizing profit (Hochman et al, 2016; Leib et al, 2019). In the present study, we operationalized the act of asking for extra points in easy rounds as self‐serving errors, whereas the decision not to ask for extra points in difficult rounds was considered as a self‐hurting error.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, the notion that behaviors aimed at maintatining economic self-intrest require cognitive control seems to contradict findings from the vast research on unethical decisions. This body of literature has repeatedly demonstrated that unethical behavior is prevalent when people can benefit from it (Ayal et al, 2015;Ayal & Gino, 2012;Barkan et al, 2015;Bazerman & Banaji, 2004;Bazerman & Gino, 2012;FeldmanHall et al, 2012;Haran, 2013;Leib, Moran, et al, 2019;Leib, Pittarello, et al, 2019;Schurr & Ritov, 2016;Shalvi et al, 2011Shalvi et al, , 2015.…”
Section: Reciprocity Self-interest and Cognitive Controlmentioning
confidence: 99%